THE INFLUENCE OF CORPORATE GOVERNANCE ON INTEREST IN SAVING AT BMT UGT NUSANTARA AROASBAYA BRANCH - Muktadir, Muktadir; Bakir, Ach (Wasīlah: Journal Of Sharia Sciences, 2026)
This study aims to analyze the influence of Corporate Governance on saving interest at BMT UGT Nusantara Arosbaya Branch. The research employs a quantitative approach with an associative design to examine the relationship between Corporate Governance and customers’ saving interest. The population consisted of 2,300 saving customers, with a sample of 25 respondents selected using the Slovin formula and non-probability sampling technique. Data were collected through questionnaires using a five-point Likert scale, supported by observation and documentation. Data analysis was conducted using descriptive statistics and simple linear regression after passing validity, reliability, and classical assumption tests. The findings indicate that Corporate Governance has a positive but statistically insignificant effect on saving interest. Although customers perceive the implementation of governance principles—such as transparency, accountability, responsibility, and independence—as good, these factors are not the primary determinants of their saving decisions. Social relationships, trust, and community-based characteristics appear to play a more dominant role. This study suggests that while Corporate Governance remains essential for institutional sustainability, its impact on saving interest requires integration with service quality improvement and value-based approaches.